Cross transferability of SSR markers to endangered Cedrela species that grow in Argentinean subtropical forests, as a valuable tool for population genetic studies - Soldati, Maria Cristina; Inza, Maria Virginia; Fornes, Luis Fernando; Zelener, Noga (Elsevier, 2018)
Species of Cedrela with a high economic value from Northwest and Northeastern Argentina are severely exploited. This work evaluates whether 51 nuclear SSRs, developed to study phylogenetically close species in the Meliaceae family (Cedrela odorata, Cedrela fissilis, Swietenia humilis and Swietenia macrophylla), can be used to study C. fissilis, Cedrela balansae, Cedrela saltensis and Cedrela angustifolia. A 62.8% of the total of 194 SSRs/species combinations showed a successful, homologous and cross-species amplification. As expected, a great success in SSRs transferability among Cedrela species was observed. Twenty-one screened SSRs showed a successful amplification pattern in all target species and many of them were polymorphic (9, 13, 13 and 7 SSRs for C. fissilis, C. balansae, C. saltensis and C. angustifolia, respectively). The high number of evaluated SSRs from the Cedrela genus and Meliaceae family, allowed us to obtain a suitable set of validated markers that are highly variable and easily scored, and also identify those which were less sturdy. We were able to retain a useful set of markers for three of the target species, but not for C. angustifolia. This could be due to its greater phylogenetic and morphological distances to the other three species. The lack of SSRs developed for our target species, transforms the transferred SSRs reported here in a valuable tool to monitor the genetic consequences of forest overexploitation on Cedrela species